Pengaruh Larangan Ekspor Bauksit Terhadap Kinerja Perusahaan Tambang di Indonesia - Romi Divana Dewi; Devista Putri Sahadah; Nisa Rahmasari (Journal Economic Excellence Ibnu Sina, 2024)
Starting in June 2023, the government imposed a ban on exports of bauxite seeds. It aims to develop the value of bauxite which could subsequently boost the economy as well as the country's income. The aim of this study is to provide a better understanding of the impact of the bauxite export ban policy on the performance of mining companies in Indonesia, by comparing the company's performance before the policy and after the policy. This study uses secondary data, which is the financial data of three major companies in Indonesia as of 10 June for the period from 2018 to 2023 that exports bauxite. The research results from the paired sample t test analysis show that the ban on bauxite exports has no significant effect, which means that the policy has no negative effect on the average performance of mining companies in Indonesia.